Influence of Social Media Marketing and eWOM on Cosmetic and Fashion Brand Preferences among Female Undergraduate Students in Ikot Ekpene, Akwa Ibom State (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study investigates how social media marketing (SMM) and electronic word-of-mouth (eWOM) influence cosmetic and fashion brand preferences among female undergraduate students in Ikot Ekpene, Nigeria. The study was hinged on the Uses and Gratifications (U&G) theory. The study employed a survey research design with a sample of 388 students drawn from Ritman University and Akwa Ibom State Polytechnic. Findings revealed that 70.1% of respondents reported high awareness of cosmetic and fashion brand marketing on social media, while 61.6% were confident in using these platforms to discover such brands. Engagement was moderately strong, with 55.6% actively interacting with brand content and 47.9% indicating continued interest. However, 33.7% were unwilling to maintain ongoing engagement. Factors influencing brand preference included perceived product quality (52.8%), transactional security (55.2%), and convenience (46.4%). Trust in online brands was more divided, with 47.9% expressing trust and 39.2% expressing distrust. Furthermore, brand preference was most influenced by delivery options (63.9%) and online reviews (53.3%). These findings indicate that while SMM and eWOM effectively enhance awareness and engagement, trust remains a critical barrier. The study recommends that brands prioritise trust-building mechanisms, personalised messaging, and platform-specific strategies to better engage digitally active youth consumers in semi-urban contexts